Excombatientes mutilados republicanos en Francia : el asociacionismo como defensa - Matilde Eiroa (Amnis)
The defeated of the Spanish Civil War constituted a large group with diverse profiles and conditions. Among them are the specific victims, the ex-combatants and civilians who were maimed and disabled, some of whom went into exile. This research analyses their situation on arrival in France, where they soon found themselves immersed in a new war that affected them deeply. The continuation of the associationism within the framework of the The League of Mutilated and War Invalids of the Army of the Republic, born in 1938, was considered the channel to claim the improvement of their living conditions. The results point to a recovery began to take place slowly from 1945 onwards thanks to the persistent work carried out by the association